2012
DOI: 10.1016/j.jcrs.2012.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Comparability and repeatability of corneal astigmatism measurements using different measurement technologies

Abstract: Vector analysis showed comparable corneal astigmatism measurements using automated, manual, and simulated keratometry. Pentacam equivalent K values were not comparable with those of the other keratometers. The repeatability of astigmatism magnitudes was acceptable; however, the repeatability of astigmatism meridians was moderate. The SMI Reference Unit showed good interobserver variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 33 publications
(44 reference statements)
12
47
0
Order By: Relevance
“…This is in accordance with the findings of Visser et al, 21 who found that astigmatism measurements of six different devices, including the Lenstar and Pentacam, yielded values that were not statistically significantly different. Statistically significantly lower values were measured only when measurements of the posterior corneal surface were included with the Pentacam's equivalent keratometry values.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with the findings of Visser et al, 21 who found that astigmatism measurements of six different devices, including the Lenstar and Pentacam, yielded values that were not statistically significantly different. Statistically significantly lower values were measured only when measurements of the posterior corneal surface were included with the Pentacam's equivalent keratometry values.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that manual keratometry, automated keratometry, simulated keratometry of Placido-based corneal topography, and simulated keratometry of Scheimpflug imaging provide similar values for anterior corneal curvature (28)(29)(30) , although significant disagreement in axis location has been reported (29) . Contrarily, anterior corneal astigmatism measurements differed significantly when comparing values derived from total corneal power and equivalent keratometry to that of automated, manual, and simulated keratometry (30,31) . These three later measurements are based only on the anterior corneal surface data, while the total corneal power and equivalent keratometry are based on the measurements of both the anterior and posterior corneal curvatures.…”
Section: Devicesmentioning
confidence: 99%
“…At present, several types of keratometers are used in clinical practice; however, astigmatism measurements can differ between keratometers. [7][8][9] Thus, different keratometers might select different toricities for a given IOL. A previous study 10 showed the effect that the use of different keratometers has on the choice of a toric IOL.…”
mentioning
confidence: 99%